SISTEM PENGUPAHAN DALAM PENGELOLAAN TAMBAK DITINJAU MENURUT HUKUM ISLAM: (Studi Kasus di Kecamatan Batee Kab. Pidie) - Muhammad Mahmud (Jurnal Tahqiqa : Jurnal Ilmiah Pemikiran Hukum Islam, 2018)
This paper discusses the "System of Waiting in Pond ManagementReviewed by Islamic Law (Case Study in Batee Sub-district)." This study is tofind out about wage practices in pond management, the procedures determined bythe owners of wage farms in pond management and the provisions of Islamic lawto the wages of pond management. The research aims to obtain the description asmentioned above, the researcher use some way that is field research (FieldResearch), by using observation technique, interview, and documentation, andLibrary Research (Library Research). The results showed that wage practices inpond management were daily wage, harvest sharing with percentage and share.The owner of the pond asked the workers to manage the ponds with a prescribedwage, divide the harvest by 60-40 percent sixty percent for the owner and fortypercent for the pond management, then the manager agreed. Wages made by theowner of the pond with the manager is by way of profit sharing, this is inaccordance with the provisions of Islamic law in force.